Performance of baseplate connections in CFS storage rack systems: An experimental, numerical and theoretical study. (September 2022) - Firouzianhaij, Ahmad; Gorji Azandariani, Mojtaba; Usefi, Nima; Samali, Bijan
Abstract: The moment-rotation characteristic of a baseplate connection in cold-formed steel rack systems significantly depends on the floor anchoring arrangement and the axial compression of the uprights. Hence, this study aims to present the results of an experimental, numerical and theoretical investigation on baseplate connections of storage racks with six different anchoring configurations under various axial loads. First, the experimental results on three types of baseplates under monotonic lateral load and six different axial compression loads are presented. Then, a numerical simulation is performed and verified using the experimental test results. The validated numerical method is also utilized for evaluation of three new types of baseplates which are different in anchoring configuration. Finally, a theoretical approach is developed to determine the moment capacity and stiffness of the baseplate system. The results indicate that different anchoring arrangements result in different baseplate behaviour. In addition, the stiffness and moment capacity of the baseplate connections are influenced by the magnitude of axial compression loads. Graphical abstract: Unlabelled Image Highlights: The baseplate connections in CFS storage rack systems by the experimental method were investigated. The performance of baseplate connections in CFS was investigated. The numerical model of baseplate connections in CFS was developed to predict the uniform behaviour. The effects of key parameters on the performance of the baseplate connections in CFS were studied. Using the analytical method, was obtained the capacity of the CFS storage rack systems.